The Effects of Corruption on Government Spending in the States of Colombia (2022)
This article is framed in the literature on corruption and its effects on the economy. Particularly, we analyze the effect that corruption has on government expenditure of the governorates (main administrative agencies at the departmental level) of the states (or departments, which are administrative divisions) of Colombia for the period 2008-2018. For this purpose, a corruption indicator is constructed based on criminal punishment against civil servants, and then econometric models are used to measure the impact of corruption on education, health and infrastructure spending. The results show that the governorates with the highest risk of corruption spend more on education and infrastructure and less on health. In addition, the level of economic development also impacts the type of spending made by each governorate.